2015
DOI: 10.1080/19424280.2015.1008589
|View full text |Cite
|
Sign up to set email alerts
|

Segmented midsole hardness in the midfoot to forefoot region of running shoes alters subjective perception and biomechanics during heel-toe running revealing potential to enhance footwear

Abstract: Purpose: Dual density midsole constructions at the lateral rearfoot and medial midfoot provide opportunities to improve cushioning and stability of running shoes. By similar mechanisms, non-uniform midsole density across the medio-lateral direction at the midfoot to forefoot may allow better negotiation of different loading magnitudes of the medial and lateral midfoot to forefoot during running. Thus, the effect of segmented midsole hardness at the midfoot to forefoot of running shoes on perception and biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Studying plantar pressure on the plate locations would provide insights into plantar stress-related injuries and stability. 13 For performance aspect, the optimal pathway hypothesis proposed that better comfort perception might allow for optimal movement pathway of individual. 31…”
Section: When This Study Inserted Plates At Different Forefoot Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying plantar pressure on the plate locations would provide insights into plantar stress-related injuries and stability. 13 For performance aspect, the optimal pathway hypothesis proposed that better comfort perception might allow for optimal movement pathway of individual. 31…”
Section: When This Study Inserted Plates At Different Forefoot Regionmentioning
confidence: 99%
“…On one hand, inserting a medial stiffening only the medial aspect of forefoot region of the shoe may induce forefoot instability. 13 On the other hand, inserting plates in both medial and lateral aspects may increase lateral foot loading. 14 High loading at the lateral aspect of the foot is undesirable as it is associated with Jones fracture (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Testing took place simultaneously with biomechanical data collection, with participants filling in on the questionnaire immediately after completing the eight successful trials required for the respective shoe condition. Runners assessed six perception variables (shoe weight, fit, arch support, cushioning, stability, and over preference) on a questionnaire that had been repeatedly highlighted in some articles ( Sterzing et al, 2015 ; Tay et al, 2017 ; Bishop et al, 2020 ). Also, a 15-cm visual analog scale (VAS) was carried out; these have been previously applied for running footwear assessment ( Mündermann et al, 2002 ; Mills et al, 2010 ; Kong et al, 2015 ; Sterzing et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Runners assessed six perception variables (shoe weight, fit, arch support, cushioning, stability, and over preference) on a questionnaire that had been repeatedly highlighted in some articles ( Sterzing et al, 2015 ; Tay et al, 2017 ; Bishop et al, 2020 ). Also, a 15-cm visual analog scale (VAS) was carried out; these have been previously applied for running footwear assessment ( Mündermann et al, 2002 ; Mills et al, 2010 ; Kong et al, 2015 ; Sterzing et al, 2015 ). Participants were shown and explained both variables before each shoe condition during the initial familiarization and data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, other research has shown an inability of runners to perceive specific biomechanical characteristics of running shoes. For example, runners showed similar frontal plane ankle stability perception despite testing shoes that were designed to induce different degrees of rearfoot motion (Brauner, Sterzing, Gras, & Milani, 2009; Sterzing, Custoza, Ding, & Cheung, 2015; Sterzing, Thomsen, Ding, & Cheung, 2015). Running shoe preference is further complicated by extrinsic factors, such as aesthetics (Au & Goonetilleke, 2007; Williams & Nester, 2006), brand, and price (Clinghan, Arnold, Drew, Cochrane, & Abboud, 2008; Hennig & Schulz, 2011).…”
Section: Introductionmentioning
confidence: 99%